Writing and Jesuit Praxis. Notes from a Distant Reading of the Annual Letters of the Province of Paraguay (1632-1762) - Vega, Fabián R. (Revista de Historia Social y de las Mentalidades, 2023)
Inspired by the digital humanities, this paper carries out a distant reading of the annual letters of Jesuit Paraguay (1632-1762). All these documents contain edifying accounts of the Jesuits’ apostolic activities in this region. The textual analysis shows that the annual letters are associated with a peculiar praxis because they privileged the refe- rences to the salvific aim of the Society of Jesus and the administration of certain sacra- ments, particularly confession. It also exhibits that these documents evolved: initially centred on the GuaraniÌ missions, they focused more and more on the cities and colleges as well as specific devotional practices, such as the spiritual exercises.